The Influence of Islamic Business Ethics On The Use of OVO: A Unified Theory of Acceptance And Use of Technology 2 (UTAUT 2) Approach - Anton Priyo Nugroho; Luthfiana Karim (PT. Publikasiku Academic Solution, 2023)
During the pandemic, there was a change in people's behavior in shopping, where online shopping experienced a significant increase, accompanied by an increase in cashless transactions. However, Islamic business ethics are often forgotten by some Muslim consumers and the ethics of making transactions. Therefore, this study aims to determine the influence of Islamic business ethics on the behavior of using OVO in the community in Yogyakarta. This research is quantitative research using questionnaires as a data collection method. Furthermore, angket was developed using a continuous rating scale and distributed online using the form to 275 selected respondents using purposive sample techniques and analyzed using PLS-SEM. This research found that performance expectations, business expectations, facilitating conditions, hedonic motivation, and price did not affect the interest of the people of Yogyakarta in using OVO. Meanwhile, Islamic business ethics, social influences, and habits have a positive influence on the interest of the people of Yogyakarta in the use of OVO.